Begonia zhongyangiana, a new species of Begonia (Begoniaceae) from western China - Wang, Wen-Guang; Lang, Xiao-An; Yang, Lei-Lei; Wu, Hong; Zhang, Shou-Zhou (Phytotaxa, 2019)
Begonia zhongyangiana, a new species in Begonia sect. Platycentrum (Begoniaceae) from Motuo (SE Xizang, China), is described and illustrated. This new species is similar to B. versicolor, B. scintillans and B. smithiae, but can be distinguished by its shorter rhizome lacking or rarely with short stems when blooming, orange-yellow flowers, 2 styles and 2-loculed ovary.